Catalyst- and solvent-free mechanochemical synthesis of isoxazoles from N-hydroxybenzimidoyl chlorides and enamino carbonyl compounds. Issue 45 (8th November 2018) - Xu, Hui; Fan, Guang-Peng; Liu, Zi; Wang, Guan-Wu
Abstract: A regioselective, solvent-free and catalyst-free synthesis of isoxazoles has been successfully developed under ball milling conditions. Milling the mixtures of N -hydroxybenzimidoyl chlorides and enamino carbonyl compounds in a ball mill at a frequency of 14.6 Hz for 20–60 min afforded isoxazoles in up to 86% yields. A possible reaction mechanism leading to the formation of the observed isoxazoles is proposed. Graphical abstract: